Chronic Hexavalent Chromium Exposure Induces Cancer Stem Cell-Like Property and Tumorigenesis by Increasing c-Myc Expression. (29th August 2019) - Wang, Zhishan; Lin, Hsuan-Pei; Li, Yunfei; Tao, Hua; Yang, Ping; Xie, Jie; Maddy, Drew; Kondo, Kazuya; Yang, Chengfeng
Abstract: Hexavalent chromium [Cr(VI)] is one of the most common environmental carcinogen causing lung cancer in humans; however, the mechanism of Cr(VI) carcinogenesis remains elusive. Cancer stem cells (CSCs) are considered as cancer initiating and maintaining cells. Ours and other recent studies showed that chronic Cr(VI) exposure induces CSC-like property representing an important mechanism of Cr(VI) carcinogenesis. However, how Cr(VI) exposure induces CSC-like property remains largely unknown. In this study, we found that stably knocking down the expression of c-Myc, a proto-oncogene and one of key stemness factors playing critical roles in cancer initiation and progression, in Cr(VI)-transformed human bronchial epithelial cells [BEAS-2B-Cr(VI)] significantly decreased their CSC-like property and tumorigenicity in mice. Moreover, stably knocking down c-Myc expression in parental nontransformed BEAS-2B cells significantly impaired the capability of chronic Cr(VI) exposure to induce CSC-like property and cell transformation. It was also found that stably overexpressing c-Myc alone in parental nontransformed BEAS-2B cells is capable of causing CSC-like property and cell transformation. Mechanistic studies showed that chronic Cr(VI) exposure increases c-Myc expression by down-regulating the level of microRNA-494 (miR-494). It was further determined that overexpressing miR-494 significantly reduces Cr(VI)-induced CSC-like property, cell transformation, and tumorigenesis mainly through down-regulating c-Myc expression. Together, these findings indicate that chronic low dose Cr(VI) exposure induces CSC-like property and tumorigenesis by increasing c-Myc expression through down-regulating the level of miR-494, revealing an important role of the proto-oncogene c-Myc in Cr(VI) carcinogenesis.